HPV16 E7 inhibits HBD2 expression by down-regulation of ASK1-p38 MAPK pathway in cervical cancer - Juanjuan Liao; Shanshan Deng; Bowen Shi; Meizhen Wang; Yingying Yin; Yanli Cao; Renping Liu; Xiaotian Huang; Lixia Jiang; Qiaofa Shi (Virology Journal)
Abstract Background Recent researches indicated a down-regulation of Human beta-defensin2 (HBD2) expression in cervical cancer cells, but the mechanism and clinical significance is not clear yet. Methods In this paper, based on the data from the TCGA database, the bioinformatics analysis provided by the UALCAN server was used. The HBD2 mRNA levels were tested with RT-qPCR in cells and protein concentration in cell cultural supernatant was assayed with ELISA. When the gene of Human papillomavirus type 16 E7 oncoprotein (HPV16 E7) overexpression or knockdown, the protein expression of ASK1 and p38 MAPK was detected by Western blot. Results The bioinformatics analysis results implied that mRNA levels of HBD2 in cervical cancer were lower obviously than healthy people. HBD2 mRNA levels and protein in CaSki and SiHa cells increased obviously under the condition of HPV16 E7 gene silence. However, HBD2 mRNA and protein levels decreased significantly in C33A and CaCo2 cells not only under the conditions of treatment with HPV16 E7 gene overexpression, but also the inhibition of ASK1-p38 MAPK pathway by SB-203580 or GS-4997, or shRNA expression plasmid of ASK1 transefction. Moreover, p-ASK1(Thr845), the activity forming protein of ASK1, and p-p38, decreased in C33A and CaCo2 cells accompanied with HPV16 E7 overexpression, while p-ASK1(Ser966) protein, an inhibitory forming protein kept in a same stable levels. The completely opposite patterns of the protein expression in ASK1-p38 MAPK pathway were obtained in CaSki and SiHa cells transfected with HPV16 E7 siRNA sequence. Interestingly, statistical higher levels of phosphorylated p38 and cellular apoptosis rates, were found in SiHa cells exposed in Anisomycin than in DMSO solution. And increased HBD2 protein concentration in cell cultural supernatant and decreased cell survial rates, were confirmed in CaSki and SiHa cells treatment with Anisomycin, at the same time. Conclusions Our results implied that HPV16 E7 suppresses HBD2 expression via the inhibition of the ASK1-p38 MAPK signaling pathway, and this mechanism might be a key way of anti-tumor effect of Anisomycin. This study provided a novel insight into the expression and regulation mechanism of HBD2 in tumors and offered a possible therapeutic strategy by using defensins for cervical cancer in future.